A produção imobiliária contemporânea: região central de São Paulo entre 2007 e 2014 - Silva, Hugo Louro e (2015)
This paper analyzes the resumption of investments the private real estate on residential projects in the downtown (historical center and surrounding areas) in São Paulo, intensified before 2007, the spatial area defined by the perimeter of the Operação Urbana Centro. The rates of the Brazilian real estate market launches between 1985 and 2014 indicate an increase in the volume of new projects undertaken by the real estate market since 2004, especially in São Paulo. However, even after the regulations Operação Urbana Centro (LEI MUNICIPAL Nº 12.349, 1997 – which led to the region's Sao Paulo historic downtown the most permissive zoning of the city, in terms of construction potential and category of use); data analysis shows that only from the year 2007 there was significant increase in the production of new projects in this region by the private sector, especially for residential use. This paper aims to identify the data that prove this increase and systematize them, relating them to the regulatory frameworks and market situations affecting the real estate industry and together guide the formal private production of urban space. From a comprehensive survey of residential , hotel or joint ventures implemented at the perimeter of Operação Urbana Centro since the year 1985, through the first proposals for urban operations contemplated in the 1985 Plan of Director; the Operações Interligadas (1986) and by the PD-1988; by Operação Urbana Anhangabaú (1991); monetary stabilization of the country after 1994; by own Operação Urbana Centro (launched in 1997); by the Estatuto da Cidade (2001); the Strategic Master Plan 2002 and the Strategic Regional Plans and the corresponding Law of Use and Occupation of 2004 Solo; the Ação Centro Programme (2001-2004); the new financing arrangements launched by CEF (PAR Credit and Associative) in the early 2000s; the new regulation of real estate and the opening of capital held in the sector between the years 2005 and 2007; by the global real estate crisis of 2008, its consequences and reactions in Brazil and São Paulo context; and the Minha Casa Minha Vida (2009) and its revision (2011); getting the most recent period (after 2010), in which matured and gestated projects were launched in the immediately preceding situation; we intend to identify periods, trends and movements of recent private residential real estate production in the central region of São Paulo and to find the potential and limits of this process.